1957
DOI: 10.1111/j.1755-3768.1957.tb07694.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperplasia Interocularis Cum Dystopia Lateroversa Canthi Medialis, Blepharophimosis, Dyschromia Iridocutanea Et Dysplasia Auditiva

Abstract: Ein Kapitel, das mich schon Jahre lang beschaftigt hat, ist das komplizierte Syndrom, das ich durch Materialsammlung in den niederlandischen Taubstummenanstalten und durch ausgiebiges Literaturstudium aufstellen konnte ( 1 950. 1951). Es war zuvor noch nie als ein vollstandiges Syndrom erkannt worden. Personlich sah ich davon jetzt uber 100 Falle, der erste wurde 1947 besprochen (1948 veroffentlicht).Dieses Syndrom vereinigt eine hyperplastische Entwicklung der Interokulargegend (massiver Nasenwurzel und -riic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1962
1962
1983
1983

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…lV,17 (aged 29) was normal (interocular measures: 32, 63 and 90 mm) and had six unaffected children (V, [12][13][14][15][16][17].…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…lV,17 (aged 29) was normal (interocular measures: 32, 63 and 90 mm) and had six unaffected children (V, [12][13][14][15][16][17].…”
Section: Figmentioning
confidence: 99%
“…
In 1950-51, Waardenburg (15,16,17) showed that some well-known developmental anomalies in the interocular region associated with deafness and certain pigmentary defects constitute a syndrome which is inherited as a dominant character. The syndrome consists of the following features: lateroverse dystopia of the medial canthi (estimated penetrance, 99 O/O), prominent nose root (78 O / o ) , hyperblasia of the medial part of the eyebrows with frequent overgrowth (synophrys) (45 O/O), heterochromia iridum (25 O/O), unilateral deafness or deafmutism (20 U/O), a white hair lock (17 O/O) and, in some cases, vitiligo-like pigmentary defects of the skin.
…”
mentioning
confidence: 99%
“…The triad white coat, deafness and blue coloration of the irisunilateral or bilateralis also found among dogs and cats (Fransois 1961, Waardenburg 1957.…”
mentioning
confidence: 94%
“…Cases of the syndrome have also been shown among negroes in the form of blue eyes combined with white hairlock and deafness and dumbness (Waardenburg 1957).…”
mentioning
confidence: 97%
See 1 more Smart Citation